Study of Regulations Based On Electronic Waste Management through EPR Initiatives (International Journal of Scientific Research in Science and Technology, 2025)
The present paper deals the sources of e-waste and will be able to picturise the strengths and weaknesses of regulation in developed, developing and nearby countries vis-a-vis exploring Indian e-waste regulation and provisions of the rules and Acts. The problem due to economic causes of illegal e-waste transboundary migration and handling are addressed worldwide, enforcing regulatory compliance and eliminating the health and environmental hazards related to e-waste dismantling will remain difficult.
Keywords: E-waste; EPR; Environment